Particle atomic layer deposition of alumina for sintering yttria‐stabilized cubic zirconia. Issue 5 (3rd October 2018) - O'Toole, Rebecca J.; Bartel, Christopher J.; Kodas, Maila U.; Horrell, Alexa J.; Ricote, Sandrine; Sullivan, Neal P.; Gump, Christopher J.; Musgrave, Charles B.; Weimer, Alan W.
Abstract: The addition of aluminum oxide (Al2 O3 ) as a sintering aid to yttria‐stabilized zirconia (YSZ) reduces the required densification temperature. Sintering aids are incorporated using a number of processes which can lead to ambiguity when determining the effect of the sintering aid on the densification mechanism. In this study, a novel method for sintering aid addition, Particle Atomic Layer Deposition (ALD), was used to deposit an amorphous Al2 O3 thin film on YSZ particles. Transmission electron microscopy confirmed the deposition of conformal Al2 O3 thin films on the surface of the YSZ particles. The addition of Al2 O3 to YSZ reduced the temperature at which densification began by ~75°C, and 2.2 wt% Al2 O3 addition resulted in a minimum activation energy for the intermediate stage of densification. This concentration is well in excess of the solubility limit of Al2 O3 in YSZ, showing that Al2 O3 does not enhance the densification of YSZ solely by dissolving into the YSZ lattice and activating volume diffusion. The addition of 0.7 wt% Al2 O3 with one Particle ALD cycle enhanced the ionic conductivity of YSZ by 23% after sintering at 1350°C for 2 hours, demonstrating that dense parts with high oxygen ion conductivities can be produced after sintering at reduced temperatures. One Particle ALD cycle is a fast, easily scaled‐up process that eliminates the use of solvents and has substantial cost/performance advantages over conventional processing.